Cambium Disconnection, Rootstock, and Canopy Training Impacts on Growth and Leaf Mineral Nutrients in 'Aztec Fuji' Apple. Issue 3 (3rd July 2019) - Fallahi, Esmaeil; Fallahi, Bahar; Kiester, Michael J.; Mahdavi, Shahla
ABSTRACT: The impacts of cambium disconnection in 'Aztec Fuji' apple ( Malus x domestica Borkh) trees on two rootstocks, each with either tall spindle (TS) or central leader with four lower main scaffolds (CL) architectures, on growth and leaf minerals were studied over 2015 and 2016 seasons. Trees on Bud 9 had shorter terminal shoots, smaller trunk cross sectional area (TCSA), and lower concentrations of leaf nitrogen (N), potassium (K), magnesium (Mg), and zinc (Zn) but higher leaf calcium (Ca) and leaf percentage dry weight than those on Nic 29. Trees trained into a CL had longer terminal shoots and higher leaf N (based on a percentage dry wt), but lower leaf fresh and dry weights and percentage dry weight than did those with a TS system in 2015. Trees with a CL system had higher concentration and content of leaf K as compared to trees on TS system in 2016. Application of bark girdling in 2015 (BG15) or bark girdling in both 2015 and 2016 (BG1516) reduced concentrations of leaf N, Ca, and Mg within the same year. Trees receiving a BG15 treatment had higher concentration of leaf K in 2015.